Teams, tribes and patient safety: overcoming barriers to effective teamwork in healthcare. Issue 1061 (7th January 2014) - Weller, Jennifer; Boyd, Matt; Cumin, David
Abstract: Modern healthcare is delivered by multidisciplinary, distributed healthcare teams who rely on effective teamwork and communication to ensure effective and safe patient care. However, we know that there is an unacceptable rate of unintended patient harm, and much of this is attributed to failures in communication between health professionals. The extensive literature on teams has identified shared mental models, mutual respect and trust and closed-loop communication as the underpinning conditions required for effective teams. However, a number of challenges exist in the healthcare environment. We explore these in a framework of educational, psychological and organisational challenges to the development of effective healthcare teams. Educational interventions can promote a better understanding of the principles of teamwork, help staff understand each other's roles and perspectives, and help develop specific communication strategies, but may not be sufficient on their own. Psychological barriers, such as professional silos and hierarchies, and organisational barriers such as geographically distributed teams, can increase the chance of communication failures with the potential for patient harm. We propose a seven-step plan to overcome the barriers to effective team communication that incorporates education, psychological and organisational strategies. Recent evidence suggests that improvement in teamwork in healthcare can lead to significant gains in patient safety, measured against efficiency of care, complication rate and mortality. Interventions to improve teamwork in healthcare may be the next major advance in patient outcomes.